OPTIMALISASI KONSENTRASI SUKROSA DAN AMMONIUM SULFAT PADA PRODUKSI NATA DE CITRUS MENGGUNAKAN SARI JERUK AFKIR - Rizza ' Novita; Faizah ' Hamzah; Fajar ' Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed to explore the use of rejected citrus fruit as raw material for making nata and to obtain the best concentration of sucrose and ammonium sulfate on the characteristics of nata de citrus produced. Research conducted experiments used a Completely Randomized Design (CRD) Factorial model with two factor treatments and three replications. The first factor was the concentration of sucrose with four levels, namely 0, 2.5, 5 and 7.5% and the second factor was the concentration of ammonium sulfate with three levels, namely 0.5, 0.6 and 0.7%. The results showed interaction of sucrose and ammonium sulfate concentrations significantly affected the acquisition of the water content and reducing sugar content. Sucrose concentrations significantly affected againts the value of water content, degree of acidity (pH), thickness, wet weight, yield and reducing sugar content. The concentrations of ammonium sulfate significantly affected againts water content, thickness, wet weight, yield and reducing sugar content. The best treatment of S3A3 (7,5% sucrose and 0,7% ammonium sulfate) result the degree of water content 88,94%, degree of acidity (pH) 3,57, thickness 4,58 mm, wet weight 132,20 g, yield 30,28% and reducing sugar content 1,89% of nata de citrus was relatively better than other treatments. Keywords : sucrose, ammonium sulfate, nata de citrus, rejected citrus juice